Mixed convection of water-based nanofluids in a square enclosure heated and cooled on adjacent walls. (1st January 2014) - Öğüt, Elif Büyük; Kahveci, Kamil
This study examines the mixed convection of water-based nanofluids in a lid-driven square enclosure heated from one side and cooled from the stationary adjacent side while the other sides are kept stationary and adiabatic. The conservation equations are solved numerically for the stream function, vorticity, and temperature using the differential quadrature method. The Grashof number is kept at a constant value of 10 4 in the present study, and the Reynolds number is varied so that the Richardson number will have values in the range of 0.1 to 10. Nanoparticles volume fraction f is varied as 0%, 5% and 10% and the value of h the ratio of the nanolayer thickness to the original particle radius, is fixed to 0.1. The results show that the motion of the side wall and nanoparticle usage has significant effects on the flow and temperature fields. A significant increase in the average Nusselt number is seen with an increase in the volume fraction of nanoparticles and a decrease in the Richardson number.